Solid-waste-based multifunctional tailing asphalt pavement material and preparation method thereof

By using modified materials in tailings asphalt mixture, the high and low temperature performance, durability and self-healing performance are improved, and the problem of insufficient performance of tailings in asphalt mixture in the prior art is solved, and the further development is achieved. Stable and durable pavement materials.

CN119263698APending Publication Date: 2025-01-07NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411484743.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, it is difficult to take into account the high and low temperature performance, durability performance and self-healing performance of tailings in asphalt mixtures.

Method used

Using polyurethane modified asphalt, titanate modified iron tailings, surface-activated copper tailings powder, copper tailings sand and acetic anhydride modified wollastonite fibers, the performance of the material is improved by the modification treatment to form a Solid waste-based multifunctional tailings asphalt pavement material.

Benefits of technology

It significantly improves the high and low temperature performance, durability and self-healing performance of asphalt mixture, broadens its application range, and improves the compactness, compressive strength and slip resistance of the road surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098437890000151
    Figure BDA0005098437890000151
Patent Text Reader

Abstract

The invention discloses a solid waste-based multifunctional tailing asphalt pavement material and a preparation method thereof, and the pavement material comprises the following components in parts by mass: 4.5-5.5 parts of polyurethane modified asphalt, 45-60 parts of titanate modified iron tailings, 2-5 parts of surface activated copper tailing powder, 20-35 parts of copper tailing sand and 0.5-1.0 part of acetic anhydride modified wollastonite fiber. The high and low temperature performance, the durability and the self-healing performance of the asphalt mixture are comprehensively improved by modifying the solid waste tailing material and the asphalt, and the application range of the asphalt mixture is effectively widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road asphalt development, and relates to a solid waste-based multifunctional tailings asphalt pavement material and a preparation method thereof. Background Art

[0002] At present, tailings are mostly stored in the form of tailings dams, with a low comprehensive utilization rate. In the long run, it is easy to cause the risk of dam breach and environmental pollution. If tailings are used as road construction materials, it will not only greatly improve the utilization rate of tailings, but also save construction costs, which is in line with the purpose of increasing the application of industrial by-products in road engineering and reducing resource and energy consumption.

[0003] At present, some scholars have conducted preliminary research on the application of tailings in asphalt mixtures. However, due to the differences in technical indicators between tailings and natural aggregates, it is difficult for asphalt mixtures to take into account high and low temperature performance, durability and self-healing properties. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a solid waste-based multifunctional tailings asphalt pavement material and a preparation method thereof, thereby solving the technical problem that it is difficult for asphalt mixtures in the prior art to have both high and low temperature performance, durability and self-healing performance.

[0005] The present invention is achieved through the following technical solutions:

[0006] A solid waste-based multifunctional tailings asphalt pavement material comprises, by weight, 4.5 to 5.5 parts of polyurethane modified asphalt, 45 to 60 parts of titanate-modified iron tailings, 2 to 5 parts of surface-activated copper tailings powder, 20 to 35 parts of copper tailings sand and 0.5 to 1.0 part of acetic anhydride-modified wollastonite fiber.

[0007] Preferably, the maximum nominal particle size of the iron ore tailings is 13.2 mm.

[0008] Preferably, the copper tailings powder has a particle size range of 5 to 15 μm and a specific surface area of ​​670 to 730 m 2 / kg.

[0009] Preferably, the copper tailings sand has a particle size range of 0.075 to 4.75 mm and an angularity of 55% to 65%.

[0010] Preferably, the number average molecular weight of the wollastonite fiber is 0.7 to 1.3×10 5 , the fiber length is 4 to 8 mm.

[0011] Preferably, the grading range of the pavement material is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 90%-95%, the pass rate range of the standard sieve hole 9.5mm is 65%-75%, the pass rate range of the standard sieve hole 4.75mm is 40%-50%, the pass rate range of the standard sieve hole 2.36mm is 25%-35%, the pass rate range of the standard sieve hole 1.18mm is 20%-30%, the pass rate range of the standard sieve hole 0.6mm is 15%-20%, the pass rate range of the standard sieve hole 0.3mm is 8%-15%, the pass rate range of the standard sieve hole 0.15mm is 5%-12%, and the pass rate range of the standard sieve hole 0.075mm is 4%-8%.

[0012] The above-mentioned method for preparing a solid waste-based multifunctional tailings asphalt pavement material comprises adding titanate-modified iron tailings, surface-activated copper tailings powder, copper tailings sand and acetic anhydride-modified wollastonite fibers to the polyurethane-modified asphalt according to parts by mass, stirring evenly, and obtaining the solid waste-based multifunctional tailings asphalt pavement material.

[0013] Preferably, the preparation process of the polyurethane modified asphalt is:

[0014] S11: After mixing hexamethylene diisocyanate and polybutylene adipate, dibutyltin dilaurate is added, reflux reaction is carried out, and then dimethylolpropionic acid, N,N-dimethylformamide and acetone are added to extend the chain, and after cooling, a capping reaction is carried out to obtain a terminal isocyanate polyurethane prepolymer;

[0015] S12: adding diaminodiphenylmethane to the molten asphalt, and after shearing treatment, adding the terminal isocyanate polyurethane prepolymer, and continuing the shearing treatment to obtain the polyurethane modified asphalt.

[0016] Preferably, the preparation process of the titanate-modified iron ore tailings is:

[0017] S21: placing the iron tailings in a NaOH solution for immersion and stirring to obtain pretreated iron tailings;

[0018] S22: spraying a mixed solution of titanate and anhydrous ethanol onto the pretreated iron tailings to obtain the titanate-modified iron tailings.

[0019] Preferably, the preparation process of the acetic anhydride modified wollastonite fiber is:

[0020] S31: soaking the wollastonite fiber in acetone, washing and drying the fiber to obtain pretreated wollastonite fiber;

[0021] S32: adding the pretreated wollastonite fiber into an acetic anhydride solution and immersing the fiber at room temperature to obtain the acetic anhydride-modified wollastonite fiber.

[0022] Compared with the prior art, the present invention has the following beneficial technical effects:

[0023] The invention discloses a solid waste-based multifunctional tailings asphalt pavement material. Firstly, for the improvement of high and low temperature performance, the polyurethane-modified asphalt enhances the elasticity and toughness of the asphalt, which helps to improve the stability of the asphalt mixture at high temperatures and the crack resistance at low temperatures; the titanate-modified iron tailings make the surface of the iron tailings have oleophilic and hydrophobic properties, improve its adhesion with asphalt, thereby improving the stability of the mixture at high temperatures, and at the same time, this modification also helps to resist the erosion of the asphalt mixture by water, indirectly improving the crack resistance at low temperatures; the acetic anhydride-modified wollastonite fiber reduces the water absorption rate and oil absorption rate of the asphalt, reduces the performance degradation caused by the invasion of water or oil, and further enhances the high and low temperature stability of the asphalt mixture; secondly, for the enhancement of durability, the surface-activated copper tailings powder is used as a filler to replace the original The raw ore powder enhances the cohesion between the copper tailings powder and the asphalt, making the mixture more compact, thereby improving the durability of the road surface; in addition, the titanium ester-modified iron tailings, the surface-activated copper tailings powder, the copper tailings sand and the acetic anhydride-modified wollastonite fiber work together, not only improving the physical properties of the material, but also enhancing the long-term durability of the mixture through its special chemical properties (such as anti-ultraviolet aging effect); finally, for the improvement of self-healing performance, the polyurethane modified asphalt itself has a good elastic recovery ability, and the fillers such as the titanium ester-modified iron tailings and the acetic anhydride-modified wollastonite fiber improve the thermal conductivity and compatibility of the asphalt mixture, so that the whole system can be heated more evenly when heated by microwaves, thereby promoting the automatic repair of internal microcracks, and significantly improving the self-healing performance of the asphalt mixture. In summary, the present invention realizes the comprehensive improvement of the high and low temperature performance, durability and self-healing performance of the asphalt mixture through modified solid waste tailings materials and asphalt, and effectively broadens its scope of application.

[0024] Furthermore, the maximum nominal particle size of the iron tailings is 13.2 mm. Firstly, setting the maximum nominal particle size of the iron tailings to 13.2 mm helps to achieve a reasonable distribution of particles of different sizes in the mixture, that is, gradation design. Reasonable gradation can ensure that the mixture forms a tight structure during the compaction process, thereby improving the density and strength of the road surface; secondly, a larger particle size can provide better skeleton support, thereby helping to improve the compressive strength and shear strength of the mixture. At the same time, a reasonable particle size distribution can also improve the rutting resistance and durability of the mixture, and reduce deformation and damage of the road surface during use; in addition, a reasonable particle size setting helps to improve the drainage performance of the asphalt pavement, reduce the retention time of rainwater on the road surface, and reduce the risk of water damage. At the same time, a larger particle size can also improve the anti-skid performance of the road surface and enhance driving safety.

[0025] Furthermore, the copper tailings powder has a particle size range of 5 to 15 μm and a specific surface area of ​​670 to 730 m 2 / kg, first of all, the smaller particle size allows the copper tailings powder to be more evenly distributed in the asphalt mixture, forming a closer bond with the asphalt, thereby improving the density and strength of the mixture. The fine particles can also fill the tiny pores in the mixture, reduce the void ratio, and improve the compression, shear and permeability resistance of the road surface; the high specific surface area means that the copper tailings powder particles have more surface active points, which can more fully react physically and chemically with asphalt, enhance the adhesion between the particles and asphalt, and further improve the mechanical properties and durability of the mixture; in addition, the fine particle size and high specific surface area of ​​the copper tailings powder help to reduce the fluidity and deformation of the mixture at high temperatures and improve the thermal stability of the road surface. At the same time, its excellent physical properties can also enhance the crack resistance of the mixture at low temperatures and maintain the flatness and comfort of the road surface.

[0026] Furthermore, the particle size range of the copper tailings is 0.075-4.75 mm, and the angularity is 55%-65%. First, the particle size range of the copper tailings is set between 0.075 and 4.75 mm, which is helpful to form a reasonable particle size distribution, i.e., gradation, in the asphalt mixture. This gradation can ensure that the mixture forms a tight structure during the compaction process, reduce the void ratio, and improve the density and strength of the road surface. Particles with smaller particle sizes can fill the gaps between particles with larger particle sizes, further refine the pore structure of the mixture, and improve the overall density. In addition, reasonable particle size distribution and higher density can significantly improve the compression, shear and impermeability of the mixture. The addition of copper tailings makes the mixture more stable when subjected to vehicle loads and natural environmental effects. Moreover, the copper tailings particles with an angularity of 55%-65% have a rough surface and a good bite effect, which can enhance the mechanical locking force between particles, thereby improving the crack resistance of the mixture. Therefore, the addition of copper tailings can improve the durability of the mixture and reduce the damage caused by fatigue, wear and aging during the use of the road surface. Copper tailings particles with good angularity can increase the roughness of the road surface, improve the anti-skid performance of the road surface, and enhance driving safety.

[0027] Furthermore, the number average molecular weight of the wollastonite fiber is 0.7 to 1.3×10 5 , the fiber length is 4 to 8 mm. First of all, wollastonite fiber has excellent physical and mechanical properties. Its high modulus and high strength can effectively improve the overall strength of the mixture. When the fiber length is 4 to 8 mm, the fiber can form an effective reinforcement network in the mixture to resist external loads and improve the compressive, shear and tensile strength of the road surface. The addition of wollastonite fiber can also improve the toughness of the mixture, so that the road surface can better absorb and disperse energy when it is impacted or vibrated, and reduce the occurrence of cracks and damage. Wollastonite fiber can enhance the fatigue resistance of the mixture and reduce fatigue damage caused by repeated vehicle loads. Wollastonite fiber has good weather resistance and can resist the erosion of natural environmental factors such as ultraviolet rays, moisture and temperature changes, extending the service life of the road surface.

[0028] Furthermore, the gradation range of the pavement material is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 90%-95%, the pass rate range of the standard sieve hole 9.5mm is 65%-75%, the pass rate range of the standard sieve hole 4.75mm is 40%-50%, the pass rate range of the standard sieve hole 2.36mm is 25%-35%, the pass rate range of the standard sieve hole 1.18mm is 20%-30%, the pass rate range of the standard sieve hole 0.6mm is 15%-20%, the pass rate range of the standard sieve hole 0.3mm is 8%-15%, the pass rate range of the standard sieve hole 0.15mm is 5%-12%, and the pass rate range of the standard sieve hole 0.075mm is 4%-8%. Firstly, the setting of the gradation range ensures the reasonable distribution of particles of different particle sizes in the mixture and forms a tight skeleton structure, which helps to reduce the voids inside the mixture and improve the density and strength of the pavement. A reasonable gradation range enables the mixture to form a more compact structure during compaction, thereby improving the compression, shear and impermeability of the road surface. The setting of the gradation range helps to reduce the wear and aging of the mixture during long-term use and extend the service life of the road surface. By controlling the passing rate of large-size particles (such as 16mm, 13.2mm), it ensures that the mixture has a good skeleton support effect, thereby enhancing the stability and bearing capacity of the road surface; 9.5mm particles can balance the skeleton and filling effects of the mixture; the filling of smaller particles improves the density of the mixture.

[0029] Furthermore, the preparation process of the polyurethane modified asphalt is as follows: after mixing hexamethylene diisocyanate and polybutylene adipate, dibutyltin dilaurate is added, reflux reaction is carried out, and then dimethylolpropionic acid, N,N-dimethylformamide and acetone are added to extend the chain, and after cooling, end-capping reaction is carried out to obtain a terminal isocyanate-based polyurethane prepolymer; then diaminodiphenylmethane is added to the molten asphalt, after shearing treatment, the terminal isocyanate-based polyurethane prepolymer is added, and shearing treatment is continued to obtain the polyurethane modified asphalt. This method can significantly improve the comprehensive performance of the base asphalt, and greatly improve many aspects of performance such as high temperature stability and anti-aging performance.

[0030] Furthermore, the preparation process of the titanate-modified iron tailings is to place the iron tailings in a NaOH solution for immersion and stirring to obtain pretreated iron tailings; then spray a mixed solution of titanate and anhydrous ethanol on the pretreated iron tailings to obtain the titanate-modified iron tailings. This method can improve the problem of insufficient adhesion of iron tailings to asphalt due to the acidity of iron tailings, and improve the oleophilic and hydrophobic properties of iron tailings.

[0031] Furthermore, the preparation process of the acetic anhydride modified wollastonite fiber is to soak the wollastonite fiber in acetone, wash and dry it to obtain pretreated wollastonite fiber; then add the pretreated wollastonite fiber into acetic anhydride solution and soak it at room temperature to obtain the acetic anhydride modified wollastonite fiber. This method can effectively improve the compatibility of wollastonite fiber with asphalt, and facilitate the stable performance of its performance. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0033] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0034] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0035] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0036] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0037] The present invention provides a solid waste-based multifunctional tailings asphalt pavement material, which comprises, by weight, 4.5 to 5.5 parts of polyurethane modified asphalt, 45 to 60 parts of titanate-modified iron tailings, 2 to 5 parts of surface-activated copper tailings powder, 20 to 35 parts of copper tailings sand and 0.5 to 1.0 part of acetic anhydride-modified wollastonite fiber.

[0038] A preferred ratio is: 4.5 parts of polyurethane modified asphalt, 55 parts of titanate modified iron tailings, 33 parts of copper tailings sand, 5 parts of surface activated copper tailings powder, 1.0 part of admixture, and 1.5 parts of acetic anhydride modified wollastonite fiber.

[0039] Among them, the maximum nominal particle size of the iron tailings is 13.2 mm.

[0040] The copper tailings powder has a particle size range of 5 to 15 μm and a specific surface area of ​​670 to 730 m 2 / kg.

[0041] The copper tailings sand has a particle size range of 0.075 to 4.75 mm and an angularity of 55% to 65%.

[0042] The number average molecular weight of the wollastonite fiber is 0.7 to 1.3×10 5 , the fiber length is 4 to 8 mm.

[0043] In the present invention, the mixture gradation type is a suspended dense structure, and the maximum nominal particle size is 13.2 mm.

[0044] The grading range of the pavement material in the present invention is: the pass rate range of the standard sieve hole 16mm is 100%, the pass rate range of the standard sieve hole 13.2mm is 90% to 95%, the pass rate range of the standard sieve hole 9.5mm is 65% to 75%, the pass rate range of the standard sieve hole 4.75mm is 40% to 50%, the pass rate range of the standard sieve hole 2.36mm is 25% to 35%, the pass rate range of the standard sieve hole 1.18mm is 20% to 30%, the pass rate range of the standard sieve hole 0.6mm is 15% to 20%, the pass rate range of the standard sieve hole 0.3mm is 8% to 15%, the pass rate range of the standard sieve hole 0.15mm is 5% to 12%, and the pass rate range of the standard sieve hole 0.075mm is 4% to 8%.

[0045] The present invention also discloses a method for preparing the above-mentioned solid waste-based multifunctional tailings asphalt pavement material. According to the mass fractions, titanate-modified iron tailings, surface-activated copper tailings powder, copper tailings sand and acetic anhydride-modified wollastonite fibers are added to the polyurethane-modified asphalt, and stirred evenly to obtain the solid waste-based multifunctional tailings asphalt pavement material.

[0046] The preparation process of the polyurethane modified asphalt is:

[0047] S11: After mixing hexamethylene diisocyanate and polybutylene adipate, dibutyltin dilaurate is added, reflux reaction is carried out, and then dimethylolpropionic acid, N,N-dimethylformamide and acetone are added to extend the chain, and after cooling, a capping reaction is carried out to obtain a terminal isocyanate polyurethane prepolymer;

[0048] S12: adding diaminodiphenylmethane to the molten asphalt, and after shearing treatment, adding the terminal isocyanate polyurethane prepolymer, and continuing the shearing treatment to obtain the polyurethane modified asphalt.

[0049] A specific preparation process of polyurethane modified asphalt is as follows: weigh excess hexamethylene diisocyanate and polybutylene adipate in a three-necked flask equipped with a reflux condenser, a stirrer and a thermometer, heat to 90°C, add an appropriate amount of catalyst dibutyltin dilaurate, and react for 1 hour; add dimethylolpropionic acid, N,N-dimethylformamide and an appropriate amount of acetone, and react for 1 hour to extend the chain; cool to 70°C for end-capping reaction to obtain a terminal isocyanate polyurethane prepolymer;

[0050] The asphalt was heated and melted at 130°C, and then diaminodiphenylmethane was added and sheared at a shear rate of 1500 r / min for 30 minutes. A certain amount of prepolymer was weighed and preheated to 100°C in an oven and then added to the asphalt. The same temperature and shear rate were maintained and shearing was continued for 30 minutes to prepare polyurethane modified asphalt.

[0051] The asphalt in the present invention is 70# base asphalt or 90# base asphalt.

[0052] In the preparation process of the above-mentioned polyurethane modified asphalt, by weight, hexamethylene diisocyanate is 35-45 parts, polybutylene adipate is 30-40 parts, dihydroxymethylpropionic acid is 10-20 parts, and N,N-dimethylformamide is 10-20 parts.

[0053] More preferably, in parts by weight, the hexamethylene diisocyanate is 45 parts, polybutylene adipate is 35 parts, dimethylol propionic acid is 12 parts, and N,N-dimethylformamide is 8 parts.

[0054] The preparation process of the titanate-modified iron tailings is as follows:

[0055] S21: placing the iron tailings in a NaOH solution for immersion and stirring to obtain pretreated iron tailings;

[0056] S22: spraying a mixed solution of titanate and anhydrous ethanol onto the pretreated iron tailings to obtain the titanate-modified iron tailings.

[0057] A specific preparation process of titanate-modified iron tailings is as follows: iron tailings are mixed with 1% NaOH in a mass ratio of 3:1, immersed and stirred for 2 hours, and then placed at room temperature to dry the surface; titanate and anhydrous ethanol are stirred at a mass ratio of 1:50 at a speed of 200-300r / min at room temperature for 2 minutes to obtain a surface treatment agent; then the surface treatment agent is loaded into a pneumatic high-atomization paint spray gun, and the surface treatment agent is sprayed on the surface of the iron tailings while stirring to make the surface treatment agent evenly coated, and after the spraying is completed, the iron tailings are placed in a 60°C blast drying oven for 10 minutes to fully solidify the surface treatment agent, and then taken out, cooled to room temperature, and the iron tailings coated with the surface treatment agent are obtained;

[0058] The preparation process of the acetic anhydride modified wollastonite fiber is as follows:

[0059] S31: soaking the wollastonite fiber in acetone, washing and drying the fiber to obtain pretreated wollastonite fiber;

[0060] S32: adding the pretreated wollastonite fiber into an acetic anhydride solution and immersing the fiber at room temperature to obtain the acetic anhydride-modified wollastonite fiber.

[0061] A specific preparation process of acetic anhydride modified wollastonite fiber is as follows: soak the wollastonite fiber in acetone for 3 hours, then wash it thoroughly with distilled water and dry it in a 100°C forced air drying oven to remove stains on the fiber surface; add the dried wollastonite fiber into the acetic anhydride solution, stirring while adding until the wollastonite fiber is fully immersed in the acetic anhydride solution, treat it at room temperature for 8 hours, take it out, and dry it in a 130°C forced air drying oven to obtain wollastonite fiber with acetic anhydride on the surface, that is, modified wollastonite fiber.

[0062] The number average molecular weight of acetic anhydride in the present invention is 1.5×10 4 ~2.4×10 4 , a colorless and transparent liquid.

[0063] In addition, for the surface activation of copper tailings powder, a combination of thermal activation and mechanical activation can be used. A specific activation process is: the copper tailings powder is evenly spread into a quartz crucible, the crucible is placed in a quartz glass tube and adjusted to the center of the tube furnace; the nitrogen flow rate is fixed at 300 mL / min, the sample is heated from room temperature to 500°C at a heating rate of 20°C / min and kept warm for 1 hour; the activated copper tailings powder sample is placed in a ball mill and ground for 3 hours to obtain activated copper tailings powder. The particle size range of the activated copper tailings powder is 1-20 μm, and the specific surface area is 620-710 m 2 / kg.

[0064] The present invention adopts activated copper tailings powder instead of mineral powder as filler of asphalt mixture, so that the cohesion between asphalt and mineral material is increased, and the road surface has better compactness, thereby improving the high and low temperature water stability characteristics of asphalt mixture; after being coated with a surface treatment agent, the surface of the iron tailings has oleophilic and hydrophobic characteristics, which improves the problem of low adhesion between the acidic aggregate of the iron tailings and asphalt. The modified wollastonite fiber used in the present invention has anhydride coated on the surface, which increases its compatibility in asphalt mixture. At the same time, the low water absorption rate and low oil absorption rate of wollastonite fiber ensure the service life in asphalt mixture, the toughness can improve the low temperature crack resistance of asphalt mixture, and the low expansion coefficient ensures that the asphalt mixture can stably exert performance at high temperature. The activated copper tailings powder used in the present invention replaces mineral powder as filler of asphalt mixture, so that the cohesion between asphalt and mineral material is increased, and the road surface has better compactness, thereby improving the high temperature performance of the mixture, and the iron tailings and copper tailings synergistically produce the effect of anti-ultraviolet aging. The aggregates used in the present invention are iron tailings, copper tailings sand and copper tailings powder, which have higher iron and copper content than natural aggregates and have excellent thermal conductivity, which significantly improves the microwave heating self-healing performance of asphalt mixture.

[0065] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0066] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0067] Example 1

[0068] This embodiment provides a solid waste-based multifunctional tailings asphalt pavement material, which is made of the following raw materials, measured by weight: 4.5 parts of polyurethane-modified asphalt, 55 parts of titanate-modified iron tailings, 33 parts of copper tailings sand, 5 parts of surface-activated copper tailings powder, and 1.5 parts of acetic anhydride-modified wollastonite fiber.

[0069] The preparation method of the solid waste-based multifunctional tailings asphalt pavement material of this embodiment comprises the following steps:

[0070] Step 1: Preparation of activated copper tailings powder

[0071] The copper tailings were evenly spread in a quartz crucible, and the crucible was placed in a quartz glass tube and adjusted to the center of the tube furnace. The nitrogen flow rate was fixed at 300 ml / min, and the sample was heated from room temperature to 500°C at a heating rate of 20°C / min and kept warm for 1 hour. The activated copper tailings sample was placed in a ball mill and ground for 3 hours to obtain activated copper tailings powder. The particle size range of the activated copper tailings powder was 1-20 μm, and the specific surface area was 620-710 m 2 / kg;

[0072] Step 2: Surface treatment of iron ore tailings

[0073] The iron tailings and 1% NaOH are soaked and stirred for 2 hours at a mass ratio of 3:1, and then placed at room temperature to dry the surface; titanate and anhydrous ethanol are stirred at a mass ratio of 1:50 at a speed of 200-300r / min at room temperature for 2 minutes to obtain a surface treatment agent; the surface treatment agent is then loaded into a pneumatic high-atomization paint spray gun, and the surface treatment agent is sprayed on the surface of the iron tailings while stirring to make the surface treatment agent evenly coated, and after the spraying is completed, the iron tailings are placed in a 60°C blast drying oven for 10 minutes to fully solidify the surface treatment agent, and then taken out, cooled to room temperature, and the iron tailings coated with the surface treatment agent are obtained;

[0074] Step 3: Preparation of modified wollastonite fiber

[0075] The wollastonite fiber is soaked in acetone for 3 hours, then fully washed with distilled water and dried in a 100°C forced air drying oven to remove stains on the fiber surface; the dried wollastonite fiber is added into an acetic anhydride solution, stirred while adding until the wollastonite fiber is fully immersed in the acetic anhydride solution, treated at room temperature for 8 hours, taken out, and dried in a 130°C forced air drying oven to obtain wollastonite fiber with acetic anhydride on the surface, namely, modified wollastonite fiber;

[0076] Step 4: Preparation of polyurethane modified asphalt

[0077] Excess hexamethylene diisocyanate and polybutylene adipate were weighed in a three-necked flask equipped with a reflux condenser, a stirrer and a thermometer, the temperature was raised to 90°C, an appropriate amount of dibutyltin dilaurate catalyst was added, and the reaction was continued for 1 hour; dimethylolpropionic acid, N,N-dimethylformamide and an appropriate amount of acetone were added, and the reaction was continued for 1 hour for chain extension; the temperature was lowered to 70°C for end-capping reaction to obtain a terminal isocyanate polyurethane prepolymer;

[0078] The asphalt was heated and melted at 130°C, and then diaminodiphenylmethane was added and sheared at a shear rate of 1500 r / min for 30 minutes; a certain amount of prepolymer was weighed and preheated to 100°C in an oven, and then added to the asphalt, and the same temperature and shear rate were maintained, and the shearing was continued for 30 minutes to prepare the polyurethane modified asphalt;

[0079] Step 5: Preparation of solid waste-based multifunctional tailings asphalt pavement material:

[0080] The modified asphalt prepared in step 4 is added to the premixed aggregate in step 5, and the mixture is mixed and stirred evenly to obtain a solid waste-based multifunctional tailings asphalt pavement material.

[0081] The performance test results of this embodiment are shown in Table 1.

[0082] Example 2

[0083] This embodiment provides a solid waste-based multifunctional tailings asphalt pavement material, which is made of the following raw materials, measured by weight: 4.5 parts of polyurethane-modified asphalt, 60 parts of titanate-modified iron tailings, 29 parts of copper tailings sand, 4 parts of surface-activated copper tailings powder, and 1.5 parts of acetic anhydride-modified wollastonite fiber.

[0084] The preparation method of the solid waste-based multifunctional tailings asphalt pavement material in this embodiment is the same as the preparation method in Example 1.

[0085] The performance test results of this embodiment are shown in Table 1.

[0086] Example 3

[0087] This embodiment provides a solid waste-based multifunctional tailings asphalt pavement material, which is made of the following raw materials, measured by weight: 4 parts of polyurethane-modified asphalt, 53 parts of titanate-modified iron tailings, 36 parts of copper tailings sand, 5 parts of surface-activated copper tailings powder, and 3 parts of acetic anhydride-modified wollastonite fibers.

[0088] The preparation method of the solid waste-based multifunctional tailings asphalt pavement material in this embodiment is the same as the preparation method in Example 1.

[0089] The performance test results of this embodiment are shown in Table 1.

[0090] Example 4

[0091] This embodiment provides a solid waste-based multifunctional tailings asphalt pavement material, which is made of the following raw materials, measured by weight: 5 parts of polyurethane-modified asphalt, 59 parts of titanate-modified iron tailings, 30 parts of copper tailings sand, 4 parts of surface-activated copper tailings powder, and 1 part of acetic anhydride-modified wollastonite fiber.

[0092] The preparation method of the solid waste-based multifunctional tailings asphalt pavement material in this embodiment is the same as the preparation method in Example 1.

[0093] The performance test results of this embodiment are shown in Table 1.

[0094] Comparative Example 1

[0095] This comparative example provides a solid waste-based multifunctional tailings asphalt pavement material, the formula of which is basically the same as that of the solid waste-based multifunctional tailings asphalt pavement material in Example 2, with the only difference being that, in this comparative example, ordinary basalt aggregate is used instead of iron tailings as coarse aggregate.

[0096] The performance test results of this comparative example are shown in Table 1.

[0097] Comparative Example 2

[0098] This comparative example provides a solid waste-based multifunctional tailings asphalt pavement material, the formula of which is basically the same as that of the solid waste-based multifunctional tailings asphalt pavement material in Example 2, with the only difference being that in this comparative example, ordinary basalt aggregate is used instead of copper tailings sand as fine aggregate.

[0099] The performance test results of this comparative example are shown in Table 1.

[0100] Comparative Example 3

[0101] This comparative example provides a solid waste-based multifunctional tailings asphalt pavement material, the formula of which is basically the same as that of the solid waste-based multifunctional tailings asphalt pavement material in Example 2, with the only difference being that, in this comparative example, copper tailings powder is not used but ordinary limestone powder is used.

[0102] The performance test results of this comparative example are shown in Table 1.

[0103] Comparative Example 4

[0104] This comparative example provides a solid waste-based multifunctional tailings asphalt pavement material. The formula of this material is basically the same as the formula of the solid waste-based multifunctional tailings asphalt pavement material in Example 2. The only difference is that in this comparative example, coarse and fine aggregates are both basalt aggregates, and the mineral powder is ordinary limestone mineral powder.

[0105] The performance test results of this comparative example are shown in Table 1.

[0106] Comparative Example 5

[0107] This comparative example provides a solid waste-based multifunctional tailings asphalt pavement material, the formula of which is basically the same as that of the solid waste-based multifunctional tailings asphalt pavement material in Example 2, with the only difference being that in this comparative example, the wollastonite fiber is not modified.

[0108] The performance test results of this comparative example are shown in Table 1.

[0109] Comparative Example 6

[0110] This comparative example provides a solid waste-based multifunctional tailings asphalt pavement material, the formula of which is basically the same as the formula of the solid waste-based multifunctional tailings asphalt pavement material in Example 2, with the only difference being that in this comparative example, ordinary base asphalt is selected as the asphalt and is not modified with polyurethane.

[0111] The performance test results of this comparative example are shown in Table 1.

[0112] Comparative Example 7

[0113] This comparative example provides a solid waste-based multifunctional tailings asphalt pavement material, the formula of which is substantially the same as that of the solid waste-based multifunctional tailings asphalt pavement material in Example 2, the only difference being that in this comparative example, no modified wollastonite fiber is added.

[0114] The performance test results of this comparative example are shown in Table 1.

[0115] Comparative Example 8

[0116] The preparation method of the solid waste-based multifunctional tailings asphalt pavement material in this comparative example is basically the same as the preparation method of the solid waste-based multifunctional tailings asphalt pavement material in Example 2, with the only difference being that the iron tailings are not surface treated in this comparative example.

[0117] The performance test results of this comparative example are shown in Table 1.

[0118] Comparative Example 9

[0119] The preparation method of the solid waste-based multifunctional tailings asphalt pavement material in this comparative example is basically the same as the preparation method of the solid waste-based multifunctional tailings asphalt pavement material in Example 2. The only difference is that in this comparative example, the copper tailings powder is not activated and is only ground to reach the required particle size.

[0120] The performance test results of this comparative example are shown in Table 1.

[0121] Performance Testing

[0122] In order to verify that the asphalt pavement material of the present invention has high-temperature rutting resistance, low-temperature crack resistance and self-healing performance, test specimens were prefabricated with reference to the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTGE20-2011). After completion, the dynamic stability, bending tensile strain and TSR (freeze-thaw splitting strength ratio) of the test specimens were tested. A self-healing test was carried out based on microwave heating. The test results are shown in Table 1.

[0123] Table 1 Performance test results of solid waste-based multifunctional tailings asphalt pavement materials

[0124]

[0125] From Table 1, we can see that:

[0126] (1) By analyzing the various indicators of Example 1 and Comparative Examples 1 to 4, it can be found that when iron tailings and copper tailings are used alone, the impact amplitude of their dynamic stability, flexural strain and TSR after ultraviolet aging is not much different from that of ordinary asphalt mixtures. However, when iron tailings and copper tailings are used together as aggregates, the impact amplitude of road performance after ultraviolet aging is greatly reduced, indicating that the use of iron tailings and copper tailings in asphalt mixtures synergistically enhances the effect of anti-ultraviolet aging.

[0127] (2) By analyzing the various indicators of Examples 1 to 4 and Comparative Example 4, it can be found that the road performance indicators of the tailings asphalt mixture prepared by treating the iron tailings and copper tailings aggregates are better than those of the ordinary asphalt mixture, and after UV aging, the increase in dynamic stability and the decrease in bending strain and TSR are much smaller than those of the ordinary asphalt mixture, and have excellent resistance to UV aging. In addition, since the iron tailings and copper tailings contain a large amount of metal elements, the heat absorption capacity under microwave heating is greatly enhanced, the self-healing index is significantly improved, and it has a strong self-healing ability.

[0128] (3) By analyzing the various indicators of Example 1 and Comparative Examples 5 to 9, it can be found that the tailings asphalt mixture that has not been surface treated and activated may have insufficient adhesion to asphalt due to the difference in acidity and alkalinity compared with natural aggregates, resulting in a decrease in road performance indicators; polyurethane asphalt can improve the high-temperature stability and low-temperature crack resistance of asphalt mixture, which is significantly improved compared with the base asphalt; the high-temperature stability and low-temperature crack resistance of the tailings asphalt mixture without the addition of wollastonite fiber are significantly lower than those of the embodiment, and the road performance indicators are reduced due to the insufficient compatibility of wollastonite fiber with asphalt.

[0129] (4) Comparing the various indicators of Examples 1 to 4 with those of Examples 1 to 9, it can be found that Example 2 has the best performance in terms of comprehensive performance indicators, and the best raw material composition is: by weight: 4.5 parts of asphalt, 55 parts of iron tailings, 33 parts of copper tailings sand, 5 parts of copper tailings powder, and 1.5 parts of wollastonite fiber. In the preparation of polyurethane modified asphalt, by weight: 26 parts of hexamethylene diisocyanate, 18 parts of polybutylene adipate, 43 parts of dimethylol propionic acid, and 13 parts of N,N-dimethylformamide.

[0130] Example 4

[0131] The present invention provides a solid waste-based multifunctional tailings asphalt pavement material, which comprises, by weight, 4.5 parts of polyurethane-modified asphalt, 45 parts of titanate-modified iron tailings, 2 parts of surface-activated copper tailings powder, 20 parts of copper tailings sand and 0.5 parts of acetic anhydride-modified wollastonite fiber.

[0132] The preparation process of the above polyurethane modified asphalt is:

[0133] S11: After mixing hexamethylene diisocyanate and polybutylene adipate, dibutyltin dilaurate is added, reflux reaction is carried out, and then dimethylolpropionic acid, N,N-dimethylformamide and acetone are added to extend the chain, and after cooling, a capping reaction is carried out to obtain a terminal isocyanate polyurethane prepolymer;

[0134] S12: adding diaminodiphenylmethane to the molten asphalt, and after shearing treatment, adding the terminal isocyanate polyurethane prepolymer, and continuing the shearing treatment to obtain the polyurethane modified asphalt.

[0135] Wherein, in the preparation process of the above-mentioned polyurethane modified asphalt, by weight, hexamethylene diisocyanate is 35 parts, polybutylene adipate is 30 parts, dihydroxymethylpropionic acid is 10 parts, and N,N-dimethylformamide is 10 parts.

[0136] Example 5

[0137] The present invention provides a solid waste-based multifunctional tailings asphalt pavement material, which comprises, by weight, 5.5 parts of polyurethane-modified asphalt, 60 parts of titanate-modified iron tailings, 5 parts of surface-activated copper tailings powder, 35 parts of copper tailings sand and 1.0 part of acetic anhydride-modified wollastonite fiber.

[0138] The preparation process of the above polyurethane modified asphalt is:

[0139] S11: After mixing hexamethylene diisocyanate and polybutylene adipate, dibutyltin dilaurate is added, reflux reaction is carried out, and then dimethylolpropionic acid, N,N-dimethylformamide and acetone are added to extend the chain, and after cooling, a capping reaction is carried out to obtain a terminal isocyanate polyurethane prepolymer;

[0140] S12: adding diaminodiphenylmethane to the molten asphalt, and after shearing treatment, adding the terminal isocyanate polyurethane prepolymer, and continuing the shearing treatment to obtain the polyurethane modified asphalt.

[0141] Wherein, in the preparation process of the above-mentioned polyurethane modified asphalt, by weight, hexamethylene diisocyanate is 45 parts, polybutylene adipate is 40 parts, dihydroxymethylpropionic acid is 20 parts, and N,N-dimethylformamide is 20 parts.

[0142] Example 6

[0143] The present invention provides a solid waste-based multifunctional tailings asphalt pavement material, which comprises, by weight, 5 parts of polyurethane-modified asphalt, 50 parts of titanate-modified iron tailings, 3 parts of surface-activated copper tailings powder, 30 parts of copper tailings sand and 0.8 parts of acetic anhydride-modified wollastonite fiber.

[0144] The preparation process of the above polyurethane modified asphalt is:

[0145] S11: After mixing hexamethylene diisocyanate and polybutylene adipate, dibutyltin dilaurate is added, reflux reaction is carried out, and then dimethylolpropionic acid, N,N-dimethylformamide and acetone are added to extend the chain, and after cooling, a capping reaction is carried out to obtain a terminal isocyanate polyurethane prepolymer;

[0146] S12: adding diaminodiphenylmethane to the molten asphalt, and after shearing treatment, adding the terminal isocyanate polyurethane prepolymer, and continuing the shearing treatment to obtain the polyurethane modified asphalt.

[0147] Wherein, in the preparation process of the above-mentioned polyurethane modified asphalt, in terms of weight parts, the hexamethylene diisocyanate is 45 parts, the polybutylene adipate is 35 parts, the dihydroxymethylpropionic acid is 12 parts, and the N,N-dimethylformamide is 8 parts.

[0148] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A solid waste-based multifunctional tailings asphalt pavement material, characterized in that: Calculated by weight, it includes 4.5-5.5 parts of polyurethane modified asphalt, 45-60 parts of titanate modified iron tailings, 2-5 parts of surface activated copper tailings powder, 20-35 parts of copper tailings sand and 0.5-1.0 part of acetic anhydride modified wollastonite fiber.

2. The solid waste-based multifunctional tailings asphalt pavement material according to claim 1, characterized in that: The maximum nominal particle size of the iron ore tailings is 13.2 mm.

3. The solid waste-based multifunctional tailings asphalt pavement material according to claim 1, characterized in that: The copper tailings powder has a particle size range of 5 to 15 μm and a specific surface area of ​​670 to 730 m 2 / kg.

4. The solid waste-based multifunctional tailings asphalt pavement material according to claim 1, characterized in that: The copper tailings sand has a particle size range of 0.075 to 4.75 mm and an angularity of 55% to 65%.

5. The solid waste-based multifunctional tailings asphalt pavement material according to claim 1, characterized in that: The number average molecular weight of the wollastonite fiber is 0.7 to 1.3×10 5 , the fiber length is 4 to 8 mm.

6. The solid waste-based multifunctional tailings asphalt pavement material according to claim 1, characterized in that: The grading range of the pavement material is: the pass rate of the standard sieve hole 16mm is 100%, the pass rate of the standard sieve hole 13.2mm is 90%-95%, the pass rate of the standard sieve hole 9.5mm is 65%-75%, the pass rate of the standard sieve hole 4.75mm is 40%-50%, the pass rate of the standard sieve hole 2.36mm is 25%-35%, the pass rate of the standard sieve hole 1.18mm is 20%-30%, the pass rate of the standard sieve hole 0.6mm is 15%-20%, the pass rate of the standard sieve hole 0.3mm is 8%-15%, the pass rate of the standard sieve hole 0.15mm is 5%-12%, and the pass rate of the standard sieve hole 0.075mm is 4%-8%.

7. The method for preparing a solid waste-based multifunctional tailings asphalt pavement material according to any one of claims 1 to 6, characterized in that: According to the mass proportions, the titanate-modified iron tailings, the surface-activated copper tailings powder, the copper tailings sand and the acetic anhydride-modified wollastonite fibers are added to the polyurethane-modified asphalt and stirred evenly to obtain the solid waste-based multifunctional tailings asphalt pavement material.

8. The method for preparing a solid waste-based multifunctional tailings asphalt pavement material according to claim 7, characterized in that: The preparation process of the polyurethane modified asphalt is: S11: After mixing hexamethylene diisocyanate and polybutylene adipate, dibutyltin dilaurate is added, reflux reaction is carried out, and then dimethylolpropionic acid, N,N-dimethylformamide and acetone are added to extend the chain, and after cooling, a capping reaction is carried out to obtain a terminal isocyanate polyurethane prepolymer; S12: adding diaminodiphenylmethane to the molten asphalt, and after shearing treatment, adding the terminal isocyanate polyurethane prepolymer, and continuing the shearing treatment to obtain the polyurethane modified asphalt.

9. The method for preparing a solid waste-based multifunctional tailings asphalt pavement material according to claim 7, characterized in that: The preparation process of the titanate-modified iron tailings is as follows: S21: placing the iron tailings in a NaOH solution for immersion and stirring to obtain pretreated iron tailings; S22: spraying a mixed solution of titanate and anhydrous ethanol onto the pretreated iron tailings to obtain the titanate-modified iron tailings.

10. The method for preparing a solid waste-based multifunctional tailings asphalt pavement material according to claim 7, characterized in that: The preparation process of the acetic anhydride modified wollastonite fiber is as follows: S31: soaking the wollastonite fiber in acetone, washing and drying the fiber to obtain pretreated wollastonite fiber; S32: adding the pretreated wollastonite fiber into an acetic anhydride solution and immersing the fiber at room temperature to obtain the acetic anhydride-modified wollastonite fiber.

Citation Information

Cited By

  • Traceless repairing method for asphalt pavement cracks based on tailing sand

    CN120867159A